Dampak Media Sosial Terhadap Perilaku Pelajar Muslim Di Era Society 5.0 - Annida Nurfitri (-, 2022)
Social media is one of the phenomena that emerged along with the development of technology and innovation on the internet. The method used in this research is a descriptive method with a qualitative approach. From the data that has been presented, it can be seen that there are 3 social media that are often found positive content regarding education and da'wah, namely Instagram, Tiktok and YouTube. Of the 10 respondents stated that they more often encounter da'wah content on social media Instagram and Tik Tok. In this study, it was concluded that social media tends to have a negative impact on adolescents aged 13-20 years and can be overcome by spreading positive content on social media such as education and da'wah.